BioConserv - International Food Policy Research Institute; Bioversity International (International Food Policy Research Institute, 2005)
BioConserv is a web-based bibliography developed by researchers at the International Food Policy Research Institute (IFPRI), in collaboration with Bioversity International. It is a unique collection of literature that reflects the emerging interest of applied economists in plant and livestock biodiversity. BioConserv focuses on three major thematic categories addressed in the literature:(1) Biodiversity of crops and plants; (2) Animal genetic resources conservation and sustainable use; and (3) Biodiversity measurements. It is a searchable database (see Browse by Topic or Browse by Year). The collection is updated on a yearly basis and the goal is to gather all economics literature in the area. To attain this goal, BioConserv welcomes Submissions from researchers and interested parties. All relevant papers will be included in the yearly updates.